ANATOMICAL CHARACTERIZATION OF MEDICINAL PLANTS USING FOLDSCOPE: A PAPER BASED ORIGAMI MICROSCOPE-(NEW DIAGNOSTIC TOOL) - S., SHARMILA; K., RAMYA E.; S., MOWNIKA (International Journal of Current Pharmaceutical Research, 2019)
Objective: This study mainly focussed how foldscope can be used as an efficient viewable tool to detect in morphological and anatomical investigation of various bioactive medicinal plants. Microscope provides a beneficial instrument for visualization of living cells. Its cost is very high which is not affordable for rural based educational institutes. Foldscope is the ultra-affordable and versatile, paper microscope designed to be extremely portable, durable and to give optical quality similar to conventional research microscopes. Methods: For enhancing scientific temperament among rural children, Indian Born Scientist (Dr. Manu Prakash) has introduced an ultra-low-cost foldable origami-based approach for large-scale manufacturing of microscope, specifically demonstrating bright field, dark field and fluorescence microscopes. However, its potential as in research tool in the area of aromatic medicinal plants is still not known. The slides were prepared by own and were observed with the magnification power of 140X. Results: The result of the present study reported that the Foldcsope images revealed viable stained areas in the respective plant parts like trichomes, stomata, pollen grains, stem and leaf of different medicinal plants and indicating their live activities. Conclusion: Based on the attractive images captured from the Foldscope, the uses of foldscope were recommended to public. Previously we had organized some awareness cum demonstration programme regarding foldscope and its applications in the field of science education in the different educational institute of Erode District, Tamilnadu. Based on the clarity of images and easy handling of Foldscope the uses of origami microscope were recommended for higher studies.